2021
DOI: 10.1017/bpp.2021.23
|View full text |Cite
|
Sign up to set email alerts
|

Gaming the system: suboptimal compliance with loot box probability disclosure regulations in China

Abstract: Loot boxes provide randomized rewards in video games; their purchase is linked to disordered gambling and they are present in approximately half of UK video games. The relative novelty of loot boxes means that regulators and policymakers in various jurisdictions are still deciding how to regulate them. The People's Republic of China (PRC) is the first, and presently only, jurisdiction to legally require companies to disclose the probabilities of obtaining randomized loot box rewards – an approach that is also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(134 citation statements)
references
References 62 publications
1
131
2
Order By: Relevance
“…Presently, loot boxes are prevalent in video games, particularly on mobile platforms, e.g., Android and iOS: in 2019, 59% of the highestgrossing iPhone games in the UK contained loot boxes, whilst 36% of the 50 Highest grossing PC games on Steam contained loot boxes [14]. Compared to in the UK, which represents the Western video game market, loot boxes are significantly more prevalent in China: in 2020, 91% of the 100 highest-grossing iPhone games contained loot boxes [15]. This reflects that video game markets in different countries may implement loot boxes to different degrees.…”
Section: Paid Loot Boxes In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, loot boxes are prevalent in video games, particularly on mobile platforms, e.g., Android and iOS: in 2019, 59% of the highestgrossing iPhone games in the UK contained loot boxes, whilst 36% of the 50 Highest grossing PC games on Steam contained loot boxes [14]. Compared to in the UK, which represents the Western video game market, loot boxes are significantly more prevalent in China: in 2020, 91% of the 100 highest-grossing iPhone games contained loot boxes [15]. This reflects that video game markets in different countries may implement loot boxes to different degrees.…”
Section: Paid Loot Boxes In Contextmentioning
confidence: 99%
“…The video game industry has increasingly imposed this requirement as self-regulation, e.g., by Apple [39], Google [40], and the major hardware providers and game publishers [41]. This measure has also been adopted as law in China (presently the only country to do so), which has led to widespread compliance; however, the prominence and accessibility of disclosure have been identified as being suboptimal [15]. A survey of Chinese video game players found that 85% of loot box purchasers reported seeing probability disclosures (meaning that they have been reasonably widely seen by players); however, only 19% of this group reported spending less money on loot boxes as a result of seeing the disclosures [24].…”
Section: Potential Harms: Links With Problem Gamblingmentioning
confidence: 99%
“…Although the items revealed may appear random from the player’s perspective, they are often predetermined by game developers. This has led to questions around the lack of transparency from gaming companies in the algorithms used in loot boxes (which are often not disclosed) as well as in their strategies to use them to create competitive advantage [ 17 ]. Then, from a player’s perspective, they may feel lured and at times pressured to buy them [ 18 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, developers could make a game deliberately boring and nudge players towards loot boxes as in-game accelerator mechanisms. This has led to the observation that loot boxes are predatory and aim to manipulate the player [ 38 ] or seen as a ‘sludge’, a dark form of nudging [ 17 ]. Hence, the People’s Republic of China have legislated that the probabilities/chances of obtaining items from loot boxes is disclosed, in which Xiao et al suggest should be a standard requirement of loot boxes [ 17 ], with ethical design considerations [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation